Seasonal Variation of Aflatoxin Levels in Selected Spices Available in Retail Markets: Estimation of Exposure and Risk Assessment - Farah Naz; Francis Verpoort; Shahzad Zafar Iqbal; Nadia Naheed; Muhammad Rafique Asi (Toxins, 2022)
A total of 603 samples of selected spices from different seasons (winter and summer) were analyzed for the occurrence of aflatoxin B1 (AFB1), total AFs, and tocopherols. The findings revealed that 120 (38.7%) samples from the summer and 136 (46.4%) samples from the winter season were observed to be infected with AFB1 and a large amount of AFs. The highest means of both AFB1 and total Afs were observed in red pepper, i.e., 15.5 ± 3.90 µg/kg and 22.90 ± 4.10 µg/kg, respectively. The minimum averages of AFB1 and total AFs were observed in cloves of 6.32 ± 1.8 and 8.40 ± 1.60 µg/kg, respectively (from the winter season). The seasonal variations in the levels of the total AFs in selected spices were observed to be nonsignificant (p ≥ 0.05), except for the levels in red pepper and ginger samples, which showed significant differences (p ≤ 0.05). The maximum average of the dietary intake of Afs, 4.80 µg/day/kg, was found in ginger from the winter season in individual females. Furthermore, the findings document that the maximum level of total tocopherol, i.e., 44.8 ± 9.3 mg/100 g, was observed in black pepper from the winter season. A significant difference in the concentration of total tocopherols was observed in selected spices from the summer and the winter seasons (p ≤ 0.05).